Effect of dietary fiber supplementation on metabolic endotoxemia: a protocol for systematic review and meta-analysis of randomized clinical trials - Ranneh, Yazan; Fadel, Abdulmannan; Md Akim, Abdah; Idris, Iskandar; Ilesanmi-Oyelere, Bolaji Lilian; Ismail, Leila Cheikh (Multidisciplinary Digital Publishing Institute, 2023)
Introduction: Metabolic endotoxemia (ME) is the main cause of sub-clinical chronic inflammation, which subsequently triggers the onset of several chronic diseases. However, recent reports have indicated that dietary fiber (DF) contributes significantly to ameliorating ME and inflammation. This protocol aims to provide an outline of all procedures in synthesizing the available data on the effect of DF against ME. Methods: Following the PRISMA 2020 guidelines for preparing protocols, this protocol was registered in the International Prospective Registry of Systematic Reviews (PROSPERO) with registration number (CRD42023417833). In this review, we specifically focused on the inclusion of clinical trials that met the following criteria: they were published or available as preprints, employed random, quasi-random, or cross-over designs, and were exclusively documented in the English language. Clinical medical subject headings (MeSH) as search terms were used on prominent databases such as MEDLINE, COCHRANE library, PubMed, World Health Organization International Clinical Trials Registry Platforms, and US National Institutes of Health Ongoing Trials Register Clinicaltrials.gov. Results and discussion: This protocol will guide the exploration of articles that report changes in ME biomarkers in subjects supplemented with DF. The findings of this protocol will ensure a comprehensive evaluation of available evidence, provide a quantitative summary, identify patterns and trends, enhance statistical power, and address heterogeneity, which collectively will clarify the optimal types, doses, and duration of DF interventions for managing ME and low-grade inflammation. Ethics and dissemination: The quantitative data of clinical trials will be collected, and a meta-analysis will be performed using RevMan V.5.3 software. Therefore, no ethical approval is required.